Application of AI to Improve the Library Visitor Experience - Dewiyana, Himma; Ardiansyah, Arif; Ginting, Anita Dilosa; Tarigan, Viga Liora Ateta (Jurnal Tadwin, 2025)
Artificial intelligence technology is widely considered a catalyst for transforming the role of libraries in the digital era. This study aims to examine and analyze the application of AI technology in the library context and provide strategic recommendations for the development of AI-based library services that can optimally improve the library visitor experience. The study used a systematic literature review approach. From the results of the search and selection of articles through Google Scholar, there were 36 articles that met the criteria for further analysis. The results show that there are seven themes that can be raised as a basis for effective AI implementation in improving library services and user experience, namely: Library transformation, the role and benefits of AI technology in library services, the implementation of AI in various aspects of library services, the use of AI to personalize library services, the impact of AI on library operational efficiency, AI-based collaboration and knowledge sharing models between libraries, and challenges in implementing AI in libraries. Based on the results of the synthesis, it can be reported that AI is able to transform libraries through cataloging automation, service personalization, 24/7 interactive chatbots, and intelligent recommendation systems that improve operational efficiency and user satisfaction (smart search). AI can help librarians analyze visit data to understand user interest trends. The potential of AI creates a more engaging, efficient and meaningful visiting experience, although the implementation of AI in libraries faces challenges related to data privacy, infrastructure, and the readiness of library human resources.